Urbanization minimizes the effects of plant traits on soil provisioned ecosystem services across climatic regions. (19th June 2021) - Kotze, D. Johan; Ghosh, Subhadip; Hui, Nan; Jumpponen, Ari; Lee, Benjamin P. Y.‐H.; Lu, Changyi; Lum, Shawn; Pouyat, Richard; Szlavecz, Katalin; Wardle, David A.; Yesilonis, Ian; Zheng, Bangxiao; et al.
Abstract: An increasingly urbanized world is one of the most prominent examples of global environmental change. Across the globe, urban parks are designed and managed in a similar way, resulting in visually pleasing expansions of lawn interspersed with individually planted trees of varying appearances and functional traits. These large urban greenspaces have the capacity to provide various ecosystem services, including those associated with soil physicochemical properties. Our aim was to explore whether soil properties in urban parks diverge underneath vegetation producing labile or recalcitrant litter, and whether the impact is affected by climatic zone (from a boreal to temperate to tropical city). We also compared these properties to those in (semi)natural forests outside the cities to assess the influence of urbanization on plant‐trait effects. We showed that vegetation type affected percentage soil organic matter (OM), total carbon (C) and total nitrogen (N), but inconsistently across climatic zones. Plant‐trait effects were particularly weak in old parks in the boreal and temperate zones, whereas in young parks in these zones, soils underneath the two tree types accumulated significantly more OM, C and N compared to lawns. Within climatic zones, anthropogenic drivers dominated natural ones, with consistently lower values of organic‐matter‐related soil properties under trees producing labile or recalcitrant litter in parks compared to forests. The dominating effect of urbanization is also reflected in its ability to homogenize soil properties in parks across the three cities, especially in lawn soils and soils under trees irrespective of functional trait. Our study demonstrates that soil functions that relate to carbon and nitrogen dynamics—even in old urban greenspaces where plant–soil interactions have a long history—clearly diverged from those in natural ecosystems, implying a long‐lasting influence of anthropogenic drivers on soil ecosystem services. Abstract : Plant functional type controls percentage organic matter, total carbon and total nitrogen in urban soils, but inconsistently across a boreal, temperate and tropical city. Within these cities, anthropogenic drivers dominated natural ones, with lower values of these organic‐matter‐related soil properties under trees in parks compared to semi(natural) forest in the vicinity of the cities. We recommend the reintroduction of natural greenspace to the city as a nature‐based solution to store carbon and nutrients in these otherwise strongly disturbed systems.